2011
DOI: 10.1097/ncc.0b013e3181e4553c
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study to Examine the Feasibility and Effects of a Home-Based Aerobic Program on Reducing Fatigue in Children With Acute Lymphoblastic Leukemia

Abstract: It suggests that a home-based exercise program may reduce fatigue for ALL children who are undergoing maintenance chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
2
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 31 publications
4
111
2
15
Order By: Relevance
“…Recently , Yeh et al, [40] recorded reduced levels of fatigue (P = 0.03, Cohen's d = 0.54) among children with ALL , who completed a 6-week home-based aerobic exercise program when compared to a control group , as well as Blaauwbroek et al, [41] demonstrated reduced levels of fatigue with increased levels of physical activity (P < 0.005, Cohen's d = -0.92 and 0.94 respectively) after 10 weeks of a homebased physical activity in childhood with cancer survivors. In addition to the results of a study by Keats and CulosReed [42] who revealed a reduction in fatigue (P = 0.01, Cohen's d = 0.69) after a 16-week group of physical activity intervention in survivors of pediatric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently , Yeh et al, [40] recorded reduced levels of fatigue (P = 0.03, Cohen's d = 0.54) among children with ALL , who completed a 6-week home-based aerobic exercise program when compared to a control group , as well as Blaauwbroek et al, [41] demonstrated reduced levels of fatigue with increased levels of physical activity (P < 0.005, Cohen's d = -0.92 and 0.94 respectively) after 10 weeks of a homebased physical activity in childhood with cancer survivors. In addition to the results of a study by Keats and CulosReed [42] who revealed a reduction in fatigue (P = 0.01, Cohen's d = 0.69) after a 16-week group of physical activity intervention in survivors of pediatric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the first year of maintenance therapy should be targeted for preventive exercise and nutrition interventions, which will support the return to a healthy lifestyle. Several pilot studies have demonstrated feasibility of such an approach (23)(24)(25), but larger scale trials of efficacy are warranted. Schema for Children's Oncology Group Protocols (treated on or according to AALL0331 or AALL0232) with notation as to when corticosteroids and cranial radiation is given.…”
Section: Discussionmentioning
confidence: 99%
“…Five randomized, controlled trials have been identified (28)(29)(30)(31)33) and were ranked with evidence level "2b. " Six studies reached level "3b" as they included a control group but were not randomized (8,27,32,(34)(35)(36)). Six studies were classified level "4" (19-26) because they did not enroll a control group.…”
Section: Exercise In Pediatric Oncologymentioning
confidence: 99%
“…Review more patients (21,25,(27)(28)(29)(30)(31)(32)(33)(34). Five randomized, controlled trials have been identified (28)(29)(30)(31)33) and were ranked with evidence level "2b. "…”
Section: Exercise In Pediatric Oncologymentioning
confidence: 99%